An Analytical Study on Eschatology and Reasoning in the Light of the Qur'an and Hadith: Interpretation of Selected Verses - Taufik Taufik; Muallim Lubis (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2025)
The study of eschatology and logic in Islam represents a significant and intellectually rich area within the broader discourse of ʿAqidah (Islamic creed) and Islamic philosophy. Eschatology, derived from the Greek word eschatos meaning "last," concerns matters of the afterlife, including death, the apocalypse (al-Sāʿah), resurrection (al-Baʿth), judgment (al-Ḥisāb), heaven (Jannah), and hell (Jahannam). These concepts are elaborated extensively in both the Qur'an and the prophetic traditions (ḥadīth). Meanwhile, logic in Islam is not merely a philosophical exercise but serves as an epistemological framework for interpreting divine revelation and deducing legal and theological principles. Islamic logic (al-manṭiq) is rooted in both Greek logical tradition—particularly Aristotelian logic—as well as unique Islamic methodologies that integrate rationality with scriptural fidelity. This research aims to analyze selected verses and prophetic traditions related to eschatology and logic, with the objective of understanding not only their linguistic and theological meanings but also their practical implications for human belief systems and ethical behavior. The study employs an interpretive and analytical method (manhaj taḥlīlī wa tafsīrī), focusing on exegesis (tafsīr) of Qur’anic verses QS. Al-A'raf: 187–188 and QS. Al-An'am: 30, as well as relevant ḥadīths concerning eschatological events and rational thought. These verses were selected due to their direct references to the knowledge of the Hour (ʿilm al-sāʿah) and the human tendency to demand evidence while rejecting spiritual truth. The findings indicate that Islamic eschatology is framed not around speculative prediction but rather spiritual and moral readiness. The Qur'an clearly asserts that knowledge of the exact time of the Day of Judgment belongs solely to Allah (QS. Al-A’raf: 187), highlighting the limitations of human knowledge and emphasizing submission to divine wisdom.